Enhanced thermal and mechanical performance of polycrystalline diamond compact by introducing polycrystalline cubic boron nitride at the grain boundaries. (April 2021) - Chen, Zhaoran; Ma, Dejiang; Wang, Shanmin; Zhu, Pinwen; Tao, Qiang; Liu, Baochang
Abstract: Ti-coated diamond and cBN with TiCN as the binder were used to fabricate the TDBN-TiCN series PDC with improved heat resistance, wear resistance and impact toughness by a China-type cubic high-pressure apparatus (5.5–6.5 GPa, 1450–1650 °C) for drilling. Under high temperature and high pressure conditions, the Co in the cemented carbide substrate penetrated into the PCD layer and the binder TiCN to form a metal-ceramic binder system. It can promote the formation of polycrystalline cubic boron nitride (PcBN) from cubic boron nitride particles at the grain boundaries, and promote the TDBN-TiCN series PDC to have the performance of PCD and PcBN. Compared with the TDBN series PDC developed by our former research, the wear resistance of TDBN-TiCN series PDC increased by 17% and the impact toughness increased by 26%. In the TDBN-TiCN series PDC, some heat resistant phases, such as PcBN, TiB2 and TiN, were formed so as to enhance the initial graphitization and oxidizing temperatures to 958 °C, which was 8 °C higher than the TDBN series PDC (950 °C) and 178 °C higher than conventional PDC (780 °C). Highlights: The Co in the cemented carbide substrate penetrated into the PCD layer and TiCN to form a metal-ceramic binder system. The polycrystalline cubic boron nitride (PcBN) from cubic boron nitride particles at the grain boundaries. PcBN, TiB2 and TiN, were formed so as to enhance the initial graphitization and oxidizing temperatures to 958°C.